Customers’ Opinion on Small Scale Retail Stores: A Case Study - Rama Mohana Rao, K.; Ratna Manikyam, K. (Indian Journal of Marketing, 2013)
The Indian Retail sector is dominated by small scale retailers. The organized sector occupies only 5 per cent share in the total retail sector. The presence of millions of small scale retailers in different product categories makes one realize that a large number of people depend upon this activity. In the light of severe competition from the fast growing and more challenging big retailers in the fast changing scenario, the survival and growth of small scale retailers depends upon their ability to provide customer satisfaction. Customer loyalty and support are the pillars of success for these retailers. The present study aims to examine the opinion of customers on small scale retail establishments. The customers’ opinion on facilities, ambience factors, communication, sales promotion techniques, and service performance of small-scale retailers are ascertained and analyzed in this paper.